1965
DOI: 10.1104/pp.40.6.1116
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic processes in cytoplasmic particles of the avocado fruit. VII. Oxidative and phosphorylative activities throughout the climacteric cycle.

Abstract: (8,12).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
42
0

Year Published

1967
1967
1986
1986

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 11 publications
2
42
0
Order By: Relevance
“…Mitochondria which show respiratory control by ADP when oxidizing suiccillate, malate and(I a-ketoglutarate have thuls 1 Preliminiary reports of this w%ork have appeared (10,16) (11,12,15,24). The opportunity opened uip of followilg the variations in the oxi(lative abilities of the mitochonldria (lurinlg the overall ripening process.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondria which show respiratory control by ADP when oxidizing suiccillate, malate and(I a-ketoglutarate have thuls 1 Preliminiary reports of this w%ork have appeared (10,16) (11,12,15,24). The opportunity opened uip of followilg the variations in the oxi(lative abilities of the mitochonldria (lurinlg the overall ripening process.…”
mentioning
confidence: 99%
“…TPP (11,12,15,24). The opportunity opened uip of followilg the variations in the oxi(lative abilities of the mitochonldria (lurinlg the overall ripening process.…”
mentioning
confidence: 99%
“…The technique used throughout this study was that described by Lance et al (9) with modifications suggested by Romani and Ozelkok (22) and by Laties and Treffry (10). Each fruit was peeled, the embryo and seed coat removed, and the fruit cut into about 10 12-g pieces.…”
Section: Methodsmentioning
confidence: 99%
“…A number of proposed mechanisms have been reviewed (21). Mitochondria have been examined from several fruit including avocado (9), apple (5), and tomato (3), at various stages of the climacteric, and shown to: (a) oxidize tricarboxylic acid cycle acids at all stages; (b) exhibit respiratory control; and (c) phosphorylate efficiently at all stages of ripening. Electron micrographs show no change in the organelle morphology between preclimacteric and postclimacteric stages of avocado fruit (W. Vanderwoude and R. E. Young, personal communication).…”
mentioning
confidence: 99%
“…About 10 times more phosphate was incorporated inlto the tissue slices of cl.macteric peak fruit. Of the amounit incorporated, 1.4 % was esterified in preclimacteric slices while nearly 8 cation. Clearly, not only does phosphate enter the climacteric ,peak tissue more readily; it is also esterified more readily.…”
mentioning
confidence: 99%